Developing Islamic banking performance measures based on Maqasid al-shari’ah framework: cases of 24 selected banks' - Mustafa Omar, Mohammed; Md. Taib, Fauziah (Center for Central Banking Research and Education, Bank Indonesia, 2015)
Islamic banking has achieved remarkable growth that has surpassed the growth of the conventional banking system. Yet, studies show that the performances of Islamic banks (IBs) seem to be trailing behind the conventional banks (CBs). Is the poor performance of IBs the result of mismatch between their objectives and their performance measurement criteria or it is a reflection of their true performances? The objectives of Islamic banking had not been formally addressed. Mustafa and Taib (2009) derived the objectives of Islamic banking from Abu Zahara’s theory of the objectives of Shari’ah (Maqasid al-Shari’ah) and, based on these Shari’ah objectives, developed a model of Islamic banking performance measures. They named it as Performance Measures based on Maqasid al-Shari’ah framework or the PMMS model. This paper has tested the PMMS model on a sample 24 banks (12 IBs and 12 CBs). The twenty four banks were also evaluated using the traditional conventional financial measures. Mann-Whitney U-Test results show IBs faring well in their performances when measured using the PMMS model than when they are measured using the conventional banking performance yardstick. Policy prescriptions and recommendations for further studies are provided at the concluding section of the paper.